Effects of Hydrodynamic Slip on Rotating Magneto-Electro-Osmotic Flow through a Periodic Microfluidic System - Abdulhameed, Mohammed; Yakubu, Dauda Gulibur; Adamu, Garba Tahiru (Diffusion and defect data. Solid state data. Pt. A, Defect and diffusion forum, 2021)
The study is concerned with the effects of slip velocity on a non-uniform rotating electroosmotic flow in a micro-channel. Electroosmotic driven fluid flow is obtained by the application of a potential electric field which describes the nonlinear Poisson-Boltzmann equation. The external electric potential is applied along the x and y directions which provides the necessary driving force for the electroosmotic flow. Two semi analytical techniques were employed to obtain the solution of the nonlinear Poisson-Boltzmann equation. The first method incorporates the complex normalized function into the Laplace transform and the second method is the combination of the Laplace transform and D’Alembert technique. Further, the complex normalized function became difficult to invert in closed form, hence we resort to the use of numerical procedure based on the Stehfest's algorithm. The graphical solutions to the axial velocities on both x and y components have been obtained and analyzed for the effects of the slip parameter and the amplitude of oscillation of the micro-channel walls. The solutions show that the rotating electroosmotic flow profile and the flow rate greatly depend on time, rotating parameter and the electrokinetic width. The results also indicate that the applied electric field and the electroosmotic force, play vital role on the velocity distribution in the micro-channel. The fact is that the solutions obtained in this study synthesize most of the solutions available in the previous studies. Finally, this study will be relevant in biological applications particularly in pumping mechanism to help transport substances within different parts of the systems.